2020
DOI: 10.1128/jvi.00184-20
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis and Clathrin-Dependent Endocytosis Play Pivotal Roles for the Infectious Entry of Puumala Virus

Abstract: Viruses from the family Hantaviridae are encountered as emerging pathogens causing two life-threatening human zoonoses: hemorrhagic fever with renal syndrome (HFRS) and hantavirus cardiopulmonary syndrome (HCPS), with case fatality rates of up to 50%. Here, we comprehensively investigated entry of the Old World hantavirus Puumala virus (PUUV) into mammalian cells, showing that upon treatment with pharmacological inhibitors of macropinocytosis and clathrin-mediated endocytosis, PUUV infections are greatly reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Despite the differences observed in the required macropinocytosis-related kinases ML-7 and ML-9 between HTNV, an Old World hantavirus, and ANDV, a New World hantavirus, both viruses enter human respiratory epithelial cells using a pathway that depends on sodium proton exchangers and actin, supporting that the entry process can involve micropinocytosis [ 52 , 53 ]. HTNV and PUUV also use clathrin-dependent endocytosis for host cell entry [ 53 , 54 ]. Additionally, it has been reported that HTNV, PUUV, and the Black Creek Canal virus (BCCV) tend to preferentially enter at the apical site of epithelial and endothelial cells [ 46 , 55 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the differences observed in the required macropinocytosis-related kinases ML-7 and ML-9 between HTNV, an Old World hantavirus, and ANDV, a New World hantavirus, both viruses enter human respiratory epithelial cells using a pathway that depends on sodium proton exchangers and actin, supporting that the entry process can involve micropinocytosis [ 52 , 53 ]. HTNV and PUUV also use clathrin-dependent endocytosis for host cell entry [ 53 , 54 ]. Additionally, it has been reported that HTNV, PUUV, and the Black Creek Canal virus (BCCV) tend to preferentially enter at the apical site of epithelial and endothelial cells [ 46 , 55 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…We also found significant co-localization of N-YFP with vimentin, but not with tubulin (Figure 2, Figure 3, Figure 4), indicative of specific interactions with either actin and vimentin directly or with other cellular proteins being associated with the respective cytoskeletal structures. Previous reports have highlighted the crucial function of the cytoskeleton during hantavirus infections [5,9,15,35], however compelling evidence for direct interactions between individual hantavirus proteins and cytoskeleton proteins is scarce. Our data now strongly suggest that there could be a direct contact of N with actin and intermediate filaments, even in absence of any other viral components.…”
Section: Discussionmentioning
confidence: 99%
“…Entry of HV particles into their target cell, predominantly of the endothelial lineage [4], is mediated by the viral spike complex, a Gc/Gn heterotetramer. We and others have shown that, after engagement with their receptor, Old world hantaviruses exploit multiple entry routes to get access to the vulnerable host cell cytoplasm [5][6][7]. Subsequent virus replication takes place at the ER-Golgi intermediate compartment (ERGIC) and involves N-and RdRp-mediated cap-snatching as a prerequisite of viral translation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Puumala virus particles comprise a lipid envelope and a single-stranded, tri-segmented RNA genome that encodes for five proteins [ 3 ]: an RNA dependent RNA polymerase RdRp, the glycoproteins Gn and Gc, the non-structural protein NSs, and the nucleocapsid protein N. Entry of HV particles into their target cell, predominantly of the endothelial lineage [ 4 ], is mediated by the viral spike complex, a Gc/Gn heterotetramer. We and others have shown that, after engagement with their receptor, old-world hantaviruses exploit multiple entry routes to get access to the vulnerable host cell cytoplasm [ 5 , 6 , 7 ]. Subsequent virus replication takes place at the endoplasmic reticulum–Golgi intermediate compartment (ERGIC) and involves N- and RdRp-mediated cap-snatching as a prerequisite of viral translation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%